Designing and temperature sensing characteristics of upconversion luminescence core-shell structures with negative and positive thermal expansion. Issue 17 (1st September 2022) - He, Yanni; Zhan, Yanhong; Cun, Yangke; Bai, Xue; Zi, Yingzhu; Xu, Zan; Haider, Asif Ali; Qiu, Jianbei; Song, Zhiguo; Zhou, Dacheng; Yang, Yong; Li, Yongjin; et al.
Abstract: Generally, lanthanum ions doped positive expansion and negative expansion materials exhibit thermal quenching and enhancement of upconversion luminescence (UCL), respectively. Combining the UCL characteristics of positive expansion and negative expansion lattices is of importance for developing efficient temperature sensing systems. Here, positive expansion TiO2 :Yb 3+, Er 3+ three dimensionally ordered macroporous film was prepared by the template-assisted approach, and the Yb2 W3 O12 : Er 3+ solution was filled into the TiO2 : Yb 3+, Er 3+ three dimensionally ordered macroporous film. After secondary sintering, the shell of negative expansion Yb2 W3 O12 : Er 3+ was formed on the surface of TiO2 :Yb 3+ /Er 3+ core. Under 980 nm excitation, the red and green UCL is predominate for the spectra of TiO2 :Yb 3+ /Er 3+ core and Yb2 W3 O12 : Er 3+ shell, respectively. With the measurement temperature increasing, the green UCL from negative expansion Yb2 W3 O12 : Er 3+ shell increases, while the red UCL from positive expansion TiO2 :Yb 3+, Er 3+ core decreases. The performance of temperature sensing was characterized by the monitoring the UCL intensity ratio between 525 nm and 660 nm. The temperature sensitivity is about 1.12% K −1, which is larger than that of thermally coupled FIR technology. We believed that the present work is instructive for developing new generation temperature sensor.